Influência do ciclo estral sobre a configuração da cromatina em vesícula germinativa (VG) de oócitos caninos - Pereira, L. M.C. [UNESP]; Bersano, P. R.O. [UNESP]; Lopes, M. D. [UNESP] (My University, 2013)
In bitches, oocyte maturation rates are low and the percentage of oocytes that remain in germinal vesicle (GV) independent of culture conditions is high. The objective of this study is to evaluate the configuration and positioning of chromatin in GV oocytes from bitches in anestrus and diestrus phases. The ovaries were sliced and selected only the cumulus-oocyte complex degree (COCs) I. These were subjected to hyaluronidase solution of 2% and stained with Hoechst. Were identified four stages of chromatin configuration classified as GV-1, GV-2 and GV-3 and GV-4. The analyzed data showed a significant difference (p≤0,05) between the phases demonstrating greater proportion of GV-1 and GV-2 in anoestrus and GV-3 and GV-4 in the diestrus phase.
Influence of estrous cycle in chromatin configuration in germinal vesicle (GV) of canine oocytes
Keywords: Bitches; Configuration of chromatin; Germinal vesicle; Oocyte